Pemanfaatan Game Tower Defense Sebagai Media Edukasi Digital - Raden Hadapiningrani; Alvanov Zpalanzani (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2018)
Game is an activity that cannot be separated from human life because human beings are playing. The growth of digital game on a smartphone rapidly and widely available in the available online which is a service provider of digital applications and games. The existence of digital games on smartphones is an application shall be owned by user that is used as a partnership be, a pastime, and as medium of education. Educational activities are learning activities and receive information on a person directly or indirectly. The information provided on recipient's are knowledge or limited a short message. Tower defense game is one kind of games that can be used as education to the recipient. With structure analysis method, elements of education on tower defense games will be analyzed to be known by both the educational element.